Remembering Theodore Roosevelt - Cullinane, Michael Patrick. author. aut Link
IX, 295 p. 14 illus.
Keywords: This book sheds new light on the life and times of Theodore Roosevelt, drawing on a remarkable set of oral histories gathered in the 1950s from those who knew him. Remembering Theodore Roosevelt presents fourteen intimate interviews with Roosevelt’s friends, family, and contemporaries. Never before published, the transcripts reveal colorful details about the infamous Rough Riders, the political scene in New York City, the lives of his extended family, including the Hyde Park Roosevelts Franklin and Eleanor, and how the former president inspired successive generations. The book benefits from the author’s discerning annotations and commentary that provide the reader with lesser-known facts and a full appreciation of the oral history project. .